Shoot’em up game “Zenith of Lead” - Gray, Cortez Curtis (Kansas State University, 2021)
This paper presents an implementation for an idea within the shoot’em up (SHMUP) genre of games. It was developed to try and present a unique take on the genre. So, this paper provides a solution which is focused on designing gameplay which is as fast paced as possible while implementing some original mechanics. To do so we evaluate other games within the genre and how they could be innovated upon. We also go over the design of the game itself and how its performance metrics were evaluated. The implementation specified uses the game engine Game Maker Studio 2 to deliver on its premise.
Keywords: Shoot-em-up; Game Maker Studio 2; Video game; Zenith of Lead; Game design